Internalisasi Nilai Moderasi Beragama Melalui Pendidikan Agama Islam di SD N 2 Kapencar Kertek Wonosobo - Septiyani Septiyani; Mukromin Mukromin; Faisal Kamal (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This research uses a qualitative methodology with field research as the main research design. Observation, interview and documentation methods were used in the data collection approach. Three analytical approaches were applied: data reduction, data visualization, and drawing conclusions. Research findings show that: 1) Students of SD N 2 Kapencar Kertek Wonosobo have sufficient understanding of the importance of religious moderation, this shows that they have understood the indicators one by one, starting from the values ​​of tolerance, non-violence and local values. cultural accommodation, and national values. Because they live in an environment and school that is slightly different from other places, children may appreciate the value of tolerance in everyday life. Apart from being enthusiastic and able to preserve long-standing cultural heritage, students are also open to differences in views and are able to live in harmony and harmony. support each other without discriminating between personal ideologies. 2) Efforts made by the Islamic Religious Education teacher at SD N 2 Kapencar Kertek Wonosobo to instill the value of religious moderation through the implementation of Friday worship, 5S (Smile Greeting and Greeting with Manners), direct teaching in class through debates and lecture formats. Acquire knowledge beyond the boundaries of the classroom. 3) Findings from observations and interviews show a number of contributing factors, ranging from the provision of school facilities to local communities and cultural diversity. Meanwhile, the obstacle is a lack of enthusiasm for learning when studying Islamic Religious Education.